Nitrogen-doped carbon supported iron oxide as efficient catalysts for chemoselective hydrogenation of nitroarenes. Issue 98 (10th October 2016) - Xu, Shaodan; Yu, Deqing; Liao, Shangfu; Ye, Tao; Sheng, Huadong
Abstract : Chemoselective hydrogenation has been widely used in the production of fine chemicals, and developing heterogeneous catalysts with high activity and chemoselectivity is always a challenging topic. Abstract : Chemoselective hydrogenation has been widely used in the production of fine chemicals, and developing heterogeneous catalysts with high activity and chemoselectivity is always a challenging topic. Herein, we report a new type of catalysts synthesized from biomass-derived chitosan and non-noble iron, which is denoted as nitrogen-doped carbon supported iron (Fe/N–C). TEM and XRD characterization indicate the presence of iron species. Interestingly, the Fe/N–C catalysts exhibited excellent catalytic performances in the hydrogenation of nitroarenes, and excellent yields of target aniline products could be obtained under industrially viable conditions.